Risk of hepatocellular carcinoma in antiviral treatment-naïve chronic hepatitis B patients treated with entecavir or tenofovir disoproxil fumarate: a network meta-analysis - Ze-Hong Huang; Gui-Yang Lu; Ling-Xian Qiu; Guo-Hua Zhong; Yue Huang; Xing-Mei Yao; Xiao-Hui Liu; Shou-Jie Huang; Ting Wu; Quan Yuan; Ying-Bin Wang; Ying-Ying Su; et al. (BMC Cancer, 2022)
Abstract Background Long-term antiviral treatments are associated with a significantly lower hepatocellular carcinoma (HCC) incidence in chronic hepatitis B (CHB) patients by reducing HBV DNA concentrations. However, it is still controversial whether antiviral strategies affect HCC development in antiviral treatment-naïve CHB patients. This study aimed to estimate the incidence of HCC in antiviral treatment-naïve CHB patients who were treated with Entecavir (ETV) and Tenofovir Disoproxil Fumarate (TDF) and compare the efficacy of two treatment regimens in HCC reduction. Methods The PubMed, Embase, China National Knowledge Infrastructure, and Wanfang databases were systematically searched until June 24, 2021. The pooled incidence and 95% confidence interval of HCC were calculated by the Freeman-Tukey double arcsine transformation method. The efficacies of ETV and TDF treatments in HCC reduction were compared through a network meta-analysis. Results A total of 27 studies were identified as eligible for this systematic review. The incidence densities in the ETV and TDF treatment groups were 2.78 (95% CI: 2.21-3.40) and 2.59 (95% CI: 1.51-3.96) per 100 persons-year among patients with preexisting cirrhosis and 0.49 (95% CI: 0.32-0.68) and 0.30 (95% CI: 0.06-0.70) per 100 persons-year among patients without preexisting cirrhosis. As the proportion of CHB patients with preexisting cirrhosis increased, the incidence density of HCC also increased gradually. Compared with other Nucleos(t)ide analogs (NAs) treatments, ETV and TDF treatments significantly lowered the risk of HCC, with hazard ratios (HRs) of 0.60 (95% CI: 0.40-0.90) and 0.56 (95% CI: 0.35-0.89), respectively. However, there was no difference in the incidence density of HCC between ETV and TDF treatments (HR = 0.92, 95% CI: 0.71-1.20) regardless of preexisting cirrhosis. Conclusion ETV and TDF treatments were associated with significantly lower risks of HCC than other NAs treatments. However, no difference was observed between ETV and TDF treatments in the risk of HCC development regardless of preexisting cirrhosis among treatment-naïve CHB patients.